SWOT Analysis of The Potential for Cash Waqf in Indonesia: NVivo Approach and Literature Review - Doni Yusuf Bagaskara; Rohmadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to determine the SWOT analysis of the Potential of Cash Waqf in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review.